The Influence of Firm Characteristics on Earnings Management - Nurjannah, Ika Ayu; Bhilawa, Loggar (SIMAK, 2024)
This study aimed to examine whether factors such as firm size, managerial ownership, leverage, audit committee expertise, and audit committee tenure influence real earnings management in firms listed on the LQ45 index. A purposive sampling method was used to collect data, with a total of 64 valid observations, free of outliers. To assess how independent variables—firm size, managerial ownership, leverage, audit committee tenure, and expertise—affect the dependent variable of earnings management, multiple linear regression analysis was employed. The analysis was conducted using SPSS version 27. The findings reveal that firm size has a significant negative effect on earnings management while managerial ownership, leverage, audit committee expertise, and audit committee tenure do not have a significant impact.